Bolometric Corrections for FU Ori Object Accretion Disk Luminosities - Adolfo S. Carvalho; Lynne A. Hillenbrand (The Astrophysical Journal Letters)
The accretion luminosity of an FU Ori disk is a fundamental system parameter, but a challenging one to estimate for all but the most well-studied systems. FU Ori objects are dynamically evolving accretion disks, especially close in time to the outburst epoch. They have a complex multitemperature disk structure that results in distinctly shaped, broad spectral energy distributions (SEDs). Detailed spectroscopic analysis is required for simultaneous constraint on relevant physical parameters such as the central stellar mass, inner disk radius, disk inclination, and disk accretion rate. However, outbursting systems that are deeply embedded and/or distant may be limited to only photometric measurement and over only a narrow range of wavelengths. The bolometric corrections necessary to estimate accretion luminosities are not straightforward and in particular cannot be adopted from existing literature on isotropically radiating stars. We present bolometric corrections specific to astrophysical accretion disks for a variety of filters in ongoing and upcoming all-sky surveys.